(untitled) (Economics and region, 2025)
The article explores the growing impact of cyber threats on economic security amid the digital transformation of national economies and increasing reliance on information and communication technologies. This study emphasizes the importance of national technological infrastructure as a key enabler in strengthening cyber resilience and ensuring the stability of digital environments under conditions of hybrid threats. Using internationally recognized metrics such as the Global Cybersecurity Index (GCI) and the National Cyber Security Index (NCSI), the paper evaluates Ukraine’s current institutional and infrastructural readiness to resist cyberattacks. It highlights key areas of progress, such as improvements in technical measures and public policy development, as well as persistent vulnerabilities in organizational coordination and capacity building. The article offers a clarified definition of technological infrastructure and presents a comprehensive overview of its key components, based on international frameworks and academic sources. These include telecommunication networks, data centres, cloud services, internet exchange points (IXPs), cybersecurity response institutions (e.g., CERT-UA), and core government digital platforms. The current state and development dynamics of these components in Ukraine are analysed in detail, with emphasis on their relevance for effective threat detection, real-time incident response, and business continuity support. Furthermore, the article examines the strategic potential of Ukraine’s technological infrastructure to adapt to increasingly sophisticated and large-scale cyberattacks. Particular attention is given to the functional resilience of decentralized digital public services, the expansion of broadband infrastructure, and the operational readiness of national and sectoral CERT teams. The paper also identifies several critical constraints, including insufficient 5G deployment, reliance on imported equipment, lack of sovereign cloud capacity, and the need for systemic support for domestic cybersecurity innovations.